(untitled) (Revista Científica Compendium, 2020)
In the year 2020, framed by the world pandemic -which has affected all areas of humanity- the Human Right to Water Declaration celebrates ten years. Along with its first decade, we have had to deal with the COVID-19, an enemy that requires as a fundamental practice, washing our hands, which makes the access to water indispensable, and that shows the vulnerability of certain people, due to their lack of access to the liquid. What is the meaning of this declaration for Countries and for citizens? This article searches for answers to this question, based on documental research, which is focused on the UN Millenium Development Goals, the Human Right to Water Declaration and the Sustainable Development Goals, and how they interconnect. Also, it shows the results from three different civic organizations, which research the situation of the water service in Venezuela. Finally, it discusses the experience of Gente Del Agua Carabali, an organization created to contribute with solutions in a local scale.